The Relationship Between EFL Teachers' Personality Traits, Communication Strategies, and Work Engagement - Ding, Kunmin; Zhu, Lili; Yan, Xiujing (Frontiers in Psychology, 2022)
This review strives to shed light on the related studies on the relationship between English as a Foreign Language (EFL) teachers’ personality traits, communication strategies, and their work engagement. The positive correlation between teachers’ personality traits and work engagement has been confirmed in the review of the literature. Furthermore, studies have proved the relationship between teachers’ communication strategies and personality traits. No studies have been done on the direct relationship between teachers’ communication strategies and work engagement. However, the studies showed that some factors, such as teacher self-efficacy and willingness to communicate, can mediate the relationship between teachers’ communication strategies and work engagement. To improve the language teaching quality, the pedagogical implications are explained in the end. Some suggestions for further research are provided to expand the literature about teachers’ communication strategies, work engagement, and personality traits.